2022
DOI: 10.1002/adma.202108317
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular Ordering and Double‐Channel Carrier Generation of Nonfullerene Photovoltaics within Multi‐Length‐Scale Morphology

Abstract: and low energy loss that deliver high opencircuit voltage (V OC ) and short-circuit current (J SC ) in solar cell devices. [1,2] An ideal BHJ thin film requires a bicontinuous network morphology of tens of nanometers of domain size to ensure efficient exciton splitting and charge transport, [3] leading to an improved fill factor (FF). The crystallization of NFA molecule and conjugated polymer in mixture plays an important role in determining the thin-film morphology, [4,5] where the π-π stacking is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 55 publications
1
61
0
Order By: Relevance
“…Different to the ball-like structured fullerene electron acceptors, the state-of-the-art NFAs (e.g., Y6 series) are featured with a large planar structure, with two electron-withdrawing end groups sandwiching an electron-donating backbone core where two upper and lower alkyl chains are attached on . Although this unique structure offers high flexibility in the molecular design and renders tunable optical and electron properties for NFAs, it also leads to variable aggregation behavior of NFAs, in which NFAs can form H-, J-, and X- aggregations between two molecules, which appear as dimers with different shapes (e.g., S, W) in a three-dimensional (3D) space, further form 3D lamella or honeycomb networks for efficient charge transport, and ultimately determining the photovoltaic performance of OSCs. , Dedicated molecular design efforts including core engineering , and terminal modification , as well as alkyl chain substitution have been performed not only to optimize the optoelectronic properties of NFAs but also to regulate their aggregation behavior to further advance the PCE of their OSCs.…”
mentioning
confidence: 99%
“…Different to the ball-like structured fullerene electron acceptors, the state-of-the-art NFAs (e.g., Y6 series) are featured with a large planar structure, with two electron-withdrawing end groups sandwiching an electron-donating backbone core where two upper and lower alkyl chains are attached on . Although this unique structure offers high flexibility in the molecular design and renders tunable optical and electron properties for NFAs, it also leads to variable aggregation behavior of NFAs, in which NFAs can form H-, J-, and X- aggregations between two molecules, which appear as dimers with different shapes (e.g., S, W) in a three-dimensional (3D) space, further form 3D lamella or honeycomb networks for efficient charge transport, and ultimately determining the photovoltaic performance of OSCs. , Dedicated molecular design efforts including core engineering , and terminal modification , as well as alkyl chain substitution have been performed not only to optimize the optoelectronic properties of NFAs but also to regulate their aggregation behavior to further advance the PCE of their OSCs.…”
mentioning
confidence: 99%
“…Recently, by separately adding 1,8-diodoctane (DIO) into ITIC, 4TIC, and 6TIC neat films, Xu et al obtained more A-to-A type J-aggregation in these molecular films, where they reported a stronger inter-CT TA signal than their films without DIO. 19 On the other hand, Fig. 4e shows that the NFA molecular aggregation mode has a weak impact on the time scale of the inter-CT relaxation process.…”
Section: Resultsmentioning
confidence: 93%
“…15 To date, there has been growing recognition that an optimized aggregation mode of NFA molecules can significantly improve their photoelectric performances, such as the light absorption, 26 charge dynamics, 27 as well as the inter-CT effect. 19 In view of this, by fixing the intra-molecular electronic push-pull potential as D on = 0.6 eV, we further consider the inter-CT effect between neighboring NFA molecules with different aggregation modes: A-to-A type J-aggregation, A-to-D type J-aggregation, and D-to-D type H-aggregation (see the inset of Fig. 3a-c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations